2016
DOI: 10.1080/14767058.2016.1205031
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal steroid administration in medically uncomplicated pregnancy beyond 37 weeks of gestation for the prevention of neonatal morbidities prior to elective caesarean section: a systematic review and meta-analysis of randomised controlled trials

Abstract: Although antenatal steroid administration prior to elective caesarean section demonstrated significant benefit in the prevention of neonatal morbidities; however, one need to be cautious before it can be routinely administered because of the paucity of long-term safety data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This conclusion is endorsed by Cochrane who concludes that antenatal corticosteroids at term in elective cesarean section reduce the risk of RDS (52%), TT (57%) and NICU admission (58%) due to respiratory complications [3]. On the E. V. Rubio et al Open Journal of Obstetrics and Gynecology other hand, the results of the present study allow us to support the safety of antenatal betamethasone for pathologies that require delivery during the early-term period.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This conclusion is endorsed by Cochrane who concludes that antenatal corticosteroids at term in elective cesarean section reduce the risk of RDS (52%), TT (57%) and NICU admission (58%) due to respiratory complications [3]. On the E. V. Rubio et al Open Journal of Obstetrics and Gynecology other hand, the results of the present study allow us to support the safety of antenatal betamethasone for pathologies that require delivery during the early-term period.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, elective cesarean sections are associated with a higher risk of respiratory morbidity even in term pregnancies. Thus, neonatal morbidity has been shown to be higher in newborns whose mothers were delivered by elective cesarean section at different gestational ages [3]- [10]. In this line, the ASTECS study concluded that the prophylactic administration of betamethasone in term pregnancies (38 or more weeks) 48 hours prior to an elective cesarean section reduced TT and RDS requiring admission to the NICU versus the control group (relative risk RR = 0.46, 95% confidence interval = 0.23 -0.93) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large multinational cluster RCT of low- and middle-income countries reported higher, rather than lower, mortality among the preterm infants prenatally exposed to ACT [32]. Further, a meta-analysis examining ACT for elective cesarean section of term births concluded that although a small yet significant effect of ACT for prevention of neonatal morbidities was observed, the authors strongly cautioned against routine use of ACT because of other potential harms [33].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that although steroid administration before scheduled CD reduces the neonatal morbidities; however, routine administration of steroids prior scheduled CD should be cautiously because of long-term risks related to steroids. 20…”
Section: Discussionmentioning
confidence: 99%